Pengaruh Model Pembelajaran Course Review Horay Berbantuan Media APROGIL Terhadap Kecerdasan Naturalistik Siswa - Ari Suryawan; Muhamad Tohir; Indiati (Nusa Putra University, 2022)
This study aims to determine the effect of the Course Review Horay learning model assisted by APROGIL media on the naturalistic intelligence of fourth grade students at SD Negeri Ngasem, Tegalrejo District, Magelang Regency. The research design used was One-Group Pretest-Posttest. The subjects of this study were the fourth grade students at SD Negeri Ngasem totaling 19 children who were selected using a total sampling technique. Methods of data collection using a questionnaire. The results showed that the Course Review Horay learning model assisted by APROGIL media had a positive effect on students' naturalistic intelligence. This is evidenced by the results of the analysis of the Paired Sample T-Test on a sample with a probability value of sig (2-tailed) 0.000 <0.05. The increase in naturalistic intelligence is influenced by the implementation of the Course Review Horay syntax model and the application of media based on the student's environmental approach, so that the naturalist intelligence aspect has increased based on the calculation of the pretest and posttes